2020
DOI: 10.2147/mder.s245625
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cardiac Electronic Devices: Future Directions and Challenges</p>

Abstract: Cardiovascular implantable electronic devices (CIEDs) are essential management options for patients with brady-and tachyarrhythmias or heart failure with concomitant optimal pharmacotherapy. Despite increasing technological advances, there are still gaps in the management of CIED patients, eg, the growing number of lead-and pocket-related longterm complications, including cardiac device-related infective endocarditis, requires the greatest care. Likewise, patients with CIEDs should be monitored remotely as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 115 publications
(173 reference statements)
0
18
0
Order By: Relevance
“…Among the mAFA group, lower rates of OAC‐related bleeding (due to the mitigation of modifiable bleeding risk factors) and an increase in the use of OAC (from 63.4% to 70.2%) was observed as compared to standard care 45 . Indeed, implementing digital healthcare models into holistic care pathways of patients with AF may improve patients awareness and treatment acceptance, resulting in better outcomes and OACs compliance 46‐48 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the mAFA group, lower rates of OAC‐related bleeding (due to the mitigation of modifiable bleeding risk factors) and an increase in the use of OAC (from 63.4% to 70.2%) was observed as compared to standard care 45 . Indeed, implementing digital healthcare models into holistic care pathways of patients with AF may improve patients awareness and treatment acceptance, resulting in better outcomes and OACs compliance 46‐48 …”
Section: Discussionmentioning
confidence: 99%
“… 45 Indeed, implementing digital healthcare models into holistic care pathways of patients with AF may improve patients awareness and treatment acceptance, resulting in better outcomes and OACs compliance. 46 , 47 , 48 …”
Section: Discussionmentioning
confidence: 99%
“…Over 1,000,000 permanent pacemakers (PPMs) and 300,000 implantable cardioverter‐defibrillators (ICDs) are implanted annually worldwide 1 . Due to an expanding list of indications for cardiac implantable electrical devices (CIEDs) and the increasing incidence of conduction disorders and congestive heart failure, CIED use is expected to grow considerably throughout the next decade 2 . Since the first CIED was used in the 1950′s, commercially available devices have undergone significant technological refinement, size reduction, and the introduction of dual chamber pacing and rate‐adaptive capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…During 14.9 ± 5.4 months of follow-up, 29% of patients in the access arm and 20% of patients in the control arm reached the composite endpoint of all-cause mortality and HF hospitalizations (HR 1.52; 95% CI 0.97-2.37), showing that the use of the monitoring tool was not beneficial. Additional algorithms incorporating multiple HF related indexes such as thoracic impedance, heart sounds (S1, S3), respiratory rate and relative tidal volume, activity response and heart rate have been developed to overcome the limited efficacy of single parameters [73]. In the study by Boehmer et al [10], the device-based diagnostic algorithm combining these indexes showed 70% sensitivity in predicting impending HF decompensation.…”
Section: Heart Failure: a Major Public Health Threatmentioning
confidence: 99%